Donders revisited: Discrete or continuous temporal processing underlying reaction time distributions?. Issue 3 (28th September 2016) - Bao, Yan; Yang, Taoxi; Lin, Xiaoxiong; Pöppel, Ernst
Abstract : Differences of reaction times to specific stimulus configurations are used as indicators of cognitive processing stages. In this classical experimental paradigm, continuous temporal processing is implicitly assumed. Multimodal response distributions indicate, however, discrete time sampling, which is often masked by experimental conditions. Differences in reaction times reflect discrete temporal mechanisms that are pre‐semantically implemented and suggested to be based on entrained neural oscillations.